Health inequalities in hypertension and diabetes management among the poor in urban areas: a population survey analysis in south Korea - Young-Jee Jeon; Chung Reen Kim; Joo-Sung Park; Kyung-Hyun Choi; Myoung Joo Kang; Seung Guk Park; Young-Jin Park (BMC, 2016)
Abstract Background This study investigated whether the prevalence, awareness, treatment, and control of hypertension and diabetes differed by residential areas. In addition, the rate of good hypertension or diabetes control was examined separately in men and women, and in urban and rural areas. Methods This study used Korea National Health and Nutrition Examination V (2010-2012) data, a nationwide cross-sectional survey of general South Korean population. Residential areas were categorized into urban and rural areas. To examine differences between the residential areas in terms of prevalence, awareness, treatment, and control of hypertension and diabetes we performed a multivariate logistic regression adjusting for age, body mass index, physical activity, alcohol use, smoking, marital status, monthly income, and educational level. To investigate control of hypertension or diabetes within each residential area, we performed a subgroup analysis in both urban and rural areas. Results The prevalence of hypertension is higher among men in urban areas than among those in rural areas (OR = 0.80; 95 % CI = 0.67-0.96, reference group = urban areas). However, the subgroups did not differ in terms of diabetes prevalence, awareness, treatment, and control. Regardless of both sex and residential area, participants in good control of their hypertension and diabetes were younger. Inequality in good control of hypertension was observed in men who lived in urban (≤Elementary school, OR 0.74, 95 % CI 0.60-0.92) and rural areas (≤Elementary school, OR 0.67, 95 % CI 0.46-0.99). Inequality in health status was found in women who resided in urban areas (≤Elementary school, OR 0.53, 95 % CI 0.37-0.75). Good control of diabetes also showed inequalities in health status for both men (≤Elementary school, OR 0.61, 95 % CI 0.40-0.94; Middle/High school, OR 0.69, 95 % CI 0.49-0.96) and women in urban areas (≤1 million won, OR 0.56, 95 % CI 0.33-0.93) (Reference group = '≥College' for education and '>3 million' Korean won for income). Conclusions After correction for individual socioeconomic status, differences by residential area were not observed. However, when the participants with good disease control were divided by region, inequality was confirmed in urban residents. Therefore, differentiated health policies to resolve individual and regional health inequalities are necessary.